2010
DOI: 10.2478/s11536-010-0027-4
|View full text |Cite
|
Sign up to set email alerts
|

The effects of immunosuppressive agents on inflammatory response in septic rats

Abstract: AbstractSepsis remains a serious clinical problems resulting in high morbidity and mortality. We aimed to investigate the inflammatory response in a septic rat model treated with immunomodulator agents. We used the cecal ligature and puncture model to establish septic peritonitis in rats. Male Wistar-Albino rats were randomized into groups of seven rats each and assigned different regimens: Tacrolimus 1 mg/kg/day, cyclosporin-A 5 mg/kg/day and methylprednisolone 15 mg/kg/day. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…In a previous study, we have shown that the favorable effects of CSA on endotoxic manifestations are eliminated after pharmacologic inhibition of mitogen‐activated protein kinases (MAPK) . Other pertinent findings include (i) γ‐hydroxybutyrate reduces MAPK ERK phosphorylation in mouse cortex and hippocampus via a mechanism that involves the activation of GABA B receptors , (ii) the inflammatory response caused by systemic LPS is paralleled with MAPKs upregulation , and (iii) central pools of MAPKs are pivotal for the elicitation of the hypotensive and reduced cardiac autonomic activity in endotoxic rats . Based on these findings together, we may speculate that the reduced MAPK phosphorylation as a consequence of GABA B receptor activation might explain the mechanism by which baclofen abrogates the favorable cardiovascular actions of CSA in endotoxic rats.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In a previous study, we have shown that the favorable effects of CSA on endotoxic manifestations are eliminated after pharmacologic inhibition of mitogen‐activated protein kinases (MAPK) . Other pertinent findings include (i) γ‐hydroxybutyrate reduces MAPK ERK phosphorylation in mouse cortex and hippocampus via a mechanism that involves the activation of GABA B receptors , (ii) the inflammatory response caused by systemic LPS is paralleled with MAPKs upregulation , and (iii) central pools of MAPKs are pivotal for the elicitation of the hypotensive and reduced cardiac autonomic activity in endotoxic rats . Based on these findings together, we may speculate that the reduced MAPK phosphorylation as a consequence of GABA B receptor activation might explain the mechanism by which baclofen abrogates the favorable cardiovascular actions of CSA in endotoxic rats.…”
Section: Discussionmentioning
confidence: 88%
“…During severe infection, endotoxins initiate an intense primary immune response characterized by the release of potent proinflammatory cytokines such as the tumor necrosis factor‐alpha (TNF‐α) and interleukins (ILs). These early mediators promote the release of secondary inflammatory mediators such as arachidonic acid metabolites and nitric oxide . The peripherally produced inflammatory signal can get access to the brain either through active transport of cytokines across the blood–brain barrier or via the modulation of afferent nerves .…”
Section: Introductionmentioning
confidence: 99%
“…The use of calcineurin inhibitors (CNIs) such as cyclosporine and tacrolimus is often associated with side effects like nephrotoxicity, neurotoxicity, and hypertension 12‐14 . Calcineurin‐independent immunosuppressants like sirolimus are not nephrotoxic, but significant nephrotoxicity could arise when combined with CNIs 15,16 . Interestingly, CNIs have been shown to guard against endotoxic manifestations due to their ability to offset the production of inflammatory cytokines from lymphocytes 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Cyclosporine (CsA) is a powerful immunosuppressive and anti-inflammatory agent [ 5 ]. The ability of CsA to reduce immunologic activity within short time spans has also made it a drug of choice for the treatment of various immune-mediated disorders [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cyclosporine (CsA) is a powerful immunosuppressive and anti-inflammatory agent [ 5 ]. The ability of CsA to reduce immunologic activity within short time spans has also made it a drug of choice for the treatment of various immune-mediated disorders [ 5 ]. Some studies have shown that CsA can suppress inflammation, oxidative stress, and cellular apoptosis and thus exhibits neuroprotective functions [ 6 ].…”
Section: Introductionmentioning
confidence: 99%